Biochemical profiles of membranes from x-ray and neutron diffraction. - McCaughan, L (1982)
X-ray and neutron diffraction methods provide some information about the distribution of mass in biological membranes and lipid-water systems. Scattering density profiles obtained from these systems, however, usually are not directly interpretable in terms of the relative amounts of chemical constituents (e.g., lipid, protein, and water) as a function of position in the membrane. We demonstrate here that the combined use of x-ray and neutron-scattering profiles, together with information on the total amounts of each of the major membrane components, are sufficient to calculate unambiguously the volume fractions of these components at well-defined regions of the lamellar unit. Three cases are considered: a calculated model membrane pair, dipalmitoylphosphatidylcholine-water multilayers, and rabbit sciatic nerve myelin. For the model system, we discuss the limitations imposed by finite resolution in the diffraction patterns. For the lipid-water multilayers, we calculate water volume fractions in the hydrocarbon tail, lipid headgroup, and interlamellar regions; estimates of these values by various methods are in good agreement with our results. For the nerve myelin, we predict new results for the distribution of protein through the membrane.